Characterization of Necking Phenomena in High-Speed Experiments by Using a Single Camera - Gilles Besnard; Jean-Michel Lagrange; François Hild; Stéphane Roux; Christophe Voltz (EURASIP Journal on Image and Video Processing, 2010)
The purpose of the experiment described herein is the study of material deformation (here a cylinder) induced by explosives. During its expansion, the cylinder (initially 3 mm thick) is thinning until fracture appears. Some tens of microseconds before destruction, strain localizations occur and induce mechanical necking. To characterize the time of first localizations, 25 stereoscopic acquisitions at about 500,000 frames per second are used by resorting to a single ultra-high speed camera. The 3D reconstruction from stereoscopic movies is described. A special calibration procedure is followed, namely, the calibration target is imaged during the experiment itself. To characterize the performance of the present procedure, resolution and optical distortions are estimated. The principle of stereoscopic reconstruction of an object subjected to a high-speed experiment is then developed. This reconstruction is achieved by using a global image correlation code that exploits random markings on the object outer surface. The spatial resolution of the estimated surface is evaluated thanks to a realistic image pair synthesis. Last, the time evolution of surface roughness is estimated. It gives access to the onset of necking.